2022
DOI: 10.2147/jir.s391473
|View full text |Cite
|
Sign up to set email alerts
|

TNF-α and IL-1β Promote Renal Podocyte Injury in T2DM Rats by Decreasing Glomerular VEGF/eNOS Expression Levels and Altering Hemodynamic Parameters

Abstract: Purpose Diabetic nephropathy (DN) is a serious microvascular complication in those with type 2 diabetes mellitus (T2DM). Evidence confirms that serum tumor necrosis factor-α (TNF-α) and interleukin-1β (IL-1β) in the T2DM stage are proposed as prognostic markers for DN development, but it is unclear how they affect renal podocyte-associated nephrin and WT-1 expression. In the presence of podocyte injury, glomerular vascular endothelial growth factor (VEGF), endothelial nitric oxide synthase (eNOS) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…From the perspective of metabolic reprogramming, this study elucidates the important role of eNOS in renal injury, providing us with new ideas for further prevention and treatment of hypertensive kidney injury from the perspective of metabolic reprogramming. Multiple studies [ [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] ] have found that eNOS is closely related to hypertension, kidney injury, etc. eNOS can make an decrease in PKM2, which is an important mediator for catalyzing glycolysis and increasing the conversion of phosphoenolpyruvate (PEP) to pyruvate.…”
Section: Disscussionmentioning
confidence: 99%
“…From the perspective of metabolic reprogramming, this study elucidates the important role of eNOS in renal injury, providing us with new ideas for further prevention and treatment of hypertensive kidney injury from the perspective of metabolic reprogramming. Multiple studies [ [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] ] have found that eNOS is closely related to hypertension, kidney injury, etc. eNOS can make an decrease in PKM2, which is an important mediator for catalyzing glycolysis and increasing the conversion of phosphoenolpyruvate (PEP) to pyruvate.…”
Section: Disscussionmentioning
confidence: 99%
“…47 Tumor necrosis factor (TNF) and its receptor (TNFR) are common inflammatory factors in DN and play a critical role in the pathogenesis of DN. [48][49][50] Increased expression of TNF and TNFR is detected in various kidney cells, including tubular epithelial cells and mesangial cells, following prolonged exposure to high glucose, ROS, AGEs, and lipopolysaccharides. Inflammatory mediators, such as IL1α and IL6, can also stimulate the expression of TNF-α and its receptors in kidney cells.…”
Section: Inflammatory Response Of Renal Tubulointerstitial Cells In Dnmentioning
confidence: 99%